Evaluating spatial cognitive skills in elite pétanque athletes using a sport-specific motor-perceptual instrument - Nurul Ihsan; Sepriadi; Zulbahri; Donal Syafrianto; Amin Akbar; Rully Effendi (CV. FOUNDAE, 2026)
Background: Spatial cognitive skills, encompassing bilateral distance estimation, multi-object positional reasoning, angular spatial judgment, and navigational planning, are primary determinants of shooting performance in precision sports such as pétanque, yet no validated sport-specific instrument exists to measure these capacities in this athletic population. Aims: This study aimed to develop and validate a spatial cognitive skills instrument for elite pétanque athletes through a systematic Research and Development (R&D) approach, encompassing expert panel content validity evaluation and field effectiveness testing. Methods: An R&D design was employed across four sequential phases: preparation (systematic needs analysis and construct identification via focus group discussion), development (construction of a 15-item five-level motor-perceptual board apparatus instrument), content validation (Aiken’s V evaluation by a six-member multi-disciplinary expert panel), and field effectiveness testing (instrument administration to 57 senior pétanque Indonesian athletes, 40 males and 17 females, aged ≥ 17 years). Aiken’s V ≥ 0.75 was set as the content validity threshold. Effectiveness testing examined score distributions, difficulty gradient verification, and preliminary discriminant validity between athlete experience groups. Results: Validation by four psychologists showed that 13 items met acceptable standards, with Aiken values ranging from 0.8 to 0.9. However, two items did not meet the standards: items 7 (V = 0.70) and 14 (V = 0.65). This lower validity was also reinforced by qualitative feedback from the validators, who recommended refining the instrument's measurement range and questioned its consistency. Furthermore, validation by pétanque coaches yielded an Aiken value of 0.9, indicating satisfactory content validity. Finally, experts in sports testing and measurement also reported satisfactory results. Conclusion: The instrument demonstrated acceptable content validity for 13 of 15 items and promising field effectiveness, establishing a theoretically grounded and sport-specific Phase 1 psychometric foundation. Items 7 and 14 require targeted revision before reliability assessment, construct validity testing, and normative data development in subsequent phases.